Nanomechanics of Poly(catecholamine) Coatings in Aqueous Solutions. (2nd February 2016) - Lim, Chanoong; Huang, Jun; Kim, Sunjin; Lee, Haeshin; Zeng, Hongbo; Hwang, Dong Soo
Abstract: Mussel‐inspired self‐polymerized catecholamine coatings have been widely utilized as a versatile coating strategy that can be applied to a variety of substrates. For the first time, nanomechanical measurements and an evaluation of the contribution of primary amine groups to poly(catecholamine) coatings have been conducted using a surface‐forces apparatus. The adhesive strength between the poly(catecholamine) layers is 30‐times higher than that of a poly(catechol) coating. The origin of the strong attraction between the poly(catecholamine) layers is probably due to surface salt displacement by the primary amine, π–π stacking (the quadrupole–quadrupole interaction of indolic crosslinks), and cation–π interactions (the monopole–quadrupole interaction between positively charged amine groups and the indolic crosslinks). The contribution of the primary amine group to the catecholamine coating is vital for the design and development of mussel‐inspired catechol‐based coating materials.